The Music of Brazil in the Eyes of Anglo-American Academic Literature (Per Musi, 2018)
This paper presents an analysis of the literature on Brazilian music written in English and developed by Anglo-American researchers. Based on a critical reading of texts published in books dedicated to Brazilian music, it identifies prevalent themes and approaches in such circuits, as well as indicating recurring concepts and trends that underpin the discourses present in such texts. From this overview, interpretations emerge on the country's musicality and on how Brazil is seen by means of the study of their music. Besides a valorization of certain approaches and part of the musical production – popular music and some specific genres – many social, political and cultural conceptions surface in this context in which there is a circulation of ideas about a Brazil written in English.